Sox6 is necessary for efficient erythropoiesis in adult mice under physiological and anemia-induced stress conditions. - Bogdan Dumitriu (PLoS ONE, 2010)
BACKGROUND: Definitive erythropoiesis is a vital process throughout life. Both its basal activity under physiological conditions and its increased activity under anemia-induced stress conditions are highly stimulated by the hormone erythropoietin. The transcription factor Sox6 was previously shown to enhance fetal erythropoiesis together and beyond erythropoietin signaling, but its importance in adulthood and mechanisms of action remain unknown. We used here Sox6 conditional null mice and molecular assays to address these questions. METHODOLOGY/PRINCIPAL FINDINGS: Sox6fl/flErGFPCre adult mice, which lacked Sox6 in erythroid cells, exhibited compensated anemia, erythroid cell developmental defects, and anisocytotic, short-lived red cells under physiological conditions, proving that Sox6 promotes basal erythropoiesis. Tamoxifen treatment of Sox6fl/flCaggCreER mice induced widespread inactivation of Sox6 in a timely controlled manner and resulted in erythroblast defects before reticulocytosis, demonstrating that impaired erythropoiesis is a primary cause rather than consequence of anemia in the absence of Sox6. Twenty five percent of Sox6fl/flErGFPCre mice died 4 or 5 days after induction of acute anemia with phenylhydrazine. The others recovered slowly. They promptly increased their erythropoietin level and amplified their erythroid progenitor pool, but then exhibited severe erythroblast and reticulocyte defects. Sox6 is thus essential in the maturation phase of stress erythropoiesis that follows the erythropoietin-dependent amplification phase. Sox6 inactivation resulted in upregulation of embryonic globin genes, but embryonic globin chains remained scarce and apparently inconsequential. Sox6 inactivation also resulted in downregulation of erythroid terminal markers, including the Bcl2l1 gene for the anti-apoptotic factor Bcl-xL, and in vitro assays indicated that Sox6 directly upregulates Bcl2l1 downstream of and beyond erythropoietin signaling. CONCLUSIONS/SIGNIFICANCE: This study demonstrates that Sox6 is necessary for efficient erythropoiesis in adult mice under both basal and stress conditions. It is primarily involved in enhancing the survival rate and maturation process of erythroid cells and acts at least in part by upregulating Bcl2l1.